The challenges of estimating the human global burden of disease of antimicrobial resistant bacteria (2020)
Estimating the contribution of antimicrobial resistance (AMR) to global mortality and healthcare costs enables evaluation of interventions, informs policy decisions on resource allocation, and drives research priorities. However assembling the high quality, patient-level data required for global estimates is challenging. Capacity for accurate microbiology culture and antimicrobial susceptibility testing is woefully neglected in low and middle-income countries, and further surveillance and research on community antimicrobial usage, bias in blood culture sampling, and the contribution of co-morbidities such as diabetes is essential. International collaboration between governments, policy makers, academics, microbiologists, front-line clinicians, veterinarians, the food and agriculture industry and the public is critical to understand and tackle AMR.